Full employment: A survey of theory, empirics and policies - Andreas Lichtenberger; Philipp Heimberger; Aleksandr Arsenev; Meryem Gökten (The Vienna Institute for International Economic Studies (wiiw), 2024)
The concept of full employment is associated with diverse economic, political and social aspects. We provide a survey of theory, empirics and policy issues related to full employment. We make a novel contribution by tying together multi-dimensional aspects of full employment regarding definitions, theoretical perspectives, empirical measurements, policy debates and real-world policy programs. We distinguish: concepts of full employment that provide systematic links to price stability; minimum unemployment and maximum employment approaches; and the unfilled vacancies perspective. Furthermore, we provide and discuss different empirical measures of full employment for selected economies, and we propose a new full employment typology. Based on our survey findings, we argue that conceptualising and measuring full employment is not merely a technical task, but inevitably involves normative judgments. Finally, we discuss avenues for future research.
Keywords: B22; E24; E61; 330; full employment; NAIRU; Beveridge curve; employment; welfare states; job guarantee